Inhibition of Virus Growth by Ouabain: Effect of Ouabain on the Growth of HVJ in Chick Embryo Cells - Nagai, Yoshiyuki (1972)
The effect of ouabain (g-strophanthin), a cardiac glycoside, on the growth of several enveloped viruses was examined. It was found that the growth of HVJ (Sendai virus) in chick embryo cells was markedly inhibited by the drug at a concentration as low as 5 × 10(−5)m. A virus-inhibitory concentration of ouabain did not cause morphological changes in uninfected cells, nor did it have the capacity to inactivate virus infectivity. Ouabain interfered with the intracellular synthesis of viral macromolecules. Although viral ribonucleic acid and viral antigens were synthesized by the ouabain-treated cells, the rate of synthesis was slower, and the total amounts of these macromolecules were smaller than those in the untreated control cells. It is suggested that ouabain inhibits the function of membrane-bound Na, K-adenosine triphosphatase of the chick embryo cells and thus prevents accumulation of K ion in them. Accumulation of intracellular K ion to a certain level would be needed for events of exponential growth of virus to proceed, and ouabain might inhibit this step by preventing such accumulation of K ion. This view was supported by the finding that the concentration of K ion in the HVJ-infected cells was rapidly reduced by the treatment with ouabain, and that, when the ouabain-treated culture was shifted to a medium containing a higher concentration of K ion than normal medium, virus production started in parallel with the increase of intracellular K ion. The fact that the concentration of K ion in BHK-21 cells, which support virus growth in the presence of ouabain, is not reduced by the treatment with the drug also suggested this possibility.